Deugdzaamheid voor de buitenwacht: de gevel van het huis Cardinaal te Groningen (Bulletin KNOB, 1992)
Cardinaal House in Groningen is well-known to specialists of Netherlandish Renaissance architecture (note 1), but the sculptured decoration of the facade, which is dated 1559, has never been treated at any length. Thanks to new archival material the original owner of the house could be identified, which made it possible to discuss the facade as an expression of his status and cultural ideals.The facade of Cardinaal House (so called after its last owner, Mr. Klaas Cardinaal) is not in its original location any more. The house was demolished in 1893, but the facade was taken apart and later incorporated into the Provinciehuis, the seat of the Provincial Estates, built in Neo Renaissance style after plans by J.A. Vrijman (1917). Originally the house stood on Oude Kijk in 't Jatstraat. In all probability it was built for Pauwei Cornelis, a basketmaker, a member of the city council, and head of the city's militia guild.The facade is decorated with the heads of Alexander the Great, King David and Charlemagne. No doubt the three were intended as an abbreviated version of the Nine Worthies. This threefold triad of heroes from Antiquity, Judaism, and Christianity enjoyed an enormous popularity in the late Middle Ages and the Renaissance in literature and the visual arts both minor and monumental.Probably the theme originated ca. 1300 in courtly circles, where the Nine were regarded as exemplary knights. However, from the 1330's onwards they also found their way into a civic context. The Nine were depicted or sculptured in tribunals and council-chambers of town-halls as exemplary figures of Justice, or in buildings like guild-halls and on public works like fountains as rather general examples of good government and virtue.Originally the Groningen facade must have been crowned by a statue of the emperor Charles V. A statue known to have come from the facade, now in Winschoten, Oude Werf, cannot be the original, however, since it dates from the seventeenth century (Fig. 4). Statues of sovereigns in a civic context are usually found in town halls. Combinations of the Nine Worthies and the sovereign are also known. A good example is the so-called Hanseatic Hall in the town hall of Cologne. Here a series of statues of the Nine Worthies datable to the 1330's is crowned by a statue of the emperor between personifications of the city's two main privileges, i.e. the staple-right, the right of defence.Such images not only testify to the relation between city and sovereign, they also refer to the municipal privileges granted by him. The statue of Charles V on the Groningen facade can be considered in the same light. For both the theme of the Nine Worthies and the statue of Charles V, then, parallels can be found in a civic context. This iconography was used on a facade of an individual who played some role of importance in the city's government. With his facade he presented himself to the outside world as a well-to-do and virtuous man.